Faktor Yang Membedakan Pelayanan Jasa Antar Perusahaan Angkutan Udara Niaga Berjadwal Di Indonesia - Yuliana, Dina (Warta Penelitian Perhubungan, 2010)
Research about factors that differences in seniices of air transport has been done. Tire discriminationanalysis indicates tire differences and clnssifies the passengers into several obsenied groups. Tire aimof this research is to annlyz.e factors tlmt affect airlines choices. TI7e discrimination analysis indicatestire differences and clnssifies the passengers into seueml obsenied groups. Tire result shows that tiremost differentiating factor in standard seniices are in-flight sen1ices (newspapers, magazines, video,etc), flight frequency/ shcedule, and punctuality.